2017
DOI: 10.1139/apnm-2016-0711
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body active warm-up and inspiratory muscle warm-up do not improve running performance when carrying thoracic loads

Abstract: Whole body active warm up and inspiratory muscle warm up do not improve running performance when carrying thoracic loads Relative to baseline, pooled PImax was reduced by 9% after the time-trial, which was not different between trials (P>0.05). Time-trial performance was not different between any trials.Whole body AWU and IMW performed alone or combination have no ergogenic effect upon high intensity, short duration performance when carrying a 25 kg load in a backpack. 3 KEY WORDSInspiratory muscle warm-up, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…The subject of inspiratory and respiratory muscle warm-up has received significant attention recently (20); however this area is beyond the scope of this review and studies investigating inspiratory and respiratory muscle warm-up were excluded from this review. Likewise, although respiratory muscle training has been extensively studied in a variety of disease states, this area is beyond the scope of this review.…”
Section: Methodsmentioning
confidence: 99%
“…The subject of inspiratory and respiratory muscle warm-up has received significant attention recently (20); however this area is beyond the scope of this review and studies investigating inspiratory and respiratory muscle warm-up were excluded from this review. Likewise, although respiratory muscle training has been extensively studied in a variety of disease states, this area is beyond the scope of this review.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, specific inspiratory muscle warm-up and training methods have been applied to unloaded (rowing and swimming) and load carriage tasks to attenuate the magnitude of inspiratory muscle fatigue and improve performance (Volianitis et al 2001;Lomax, Grant, and Corbett 2011). However, inspiratory muscle warm-ups whereby the individual performs 2 x 30 sub-maximal (40% maximal inspiratory muscle pressure; PImax) inspiratory efforts prior to exercise in addition to a controlled whole body active warm-up was ineffective in eliciting an improvement in performance on a 2.4 km loaded time trial, despite transient increases in PImax, which is contradictory of unloaded performance tasks (Faghy and Brown 2017). However, six weeks of inspiratory muscle training (IMT), comprising 30 inspiratory efforts completed twice daily (50% PImax), increased baseline PImax and provided an ergogenic effect when exercising with a 25kg load compared with a double-blind placebo control (Faghy and Brown 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have not observed an improvement produced by the warming of the inspiratory muscles [61,62]; however, these studies were conducted in continuous sports modalities, which could explain the difference in results. Further studies on the possible beneficial effects of acute IMT in intermittent sports would be needed.…”
Section: Acute Treatmentmentioning
confidence: 82%